PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KABUPATEN GAYO LUES (Dengan Pendekatan Shift Share dan Location Quetient) - Afif Fulhaq; Diana Sapha A.H. (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study aims to find out how the growth of the agricultural sub-sector towards GRDP in Gayo lues Regency, and any subsector which is the basis in Gayo Lues Regency. This study uses secondary data through institutions and agencies related to the data used is the GRDP Regency of Gayo Lues data. The analysis model uses Shift Share (SS) and Location Quantient (LQ). The results of this study indicate that the subsector of agriculture is a subsector that experienced growth but experienced slow and non competitive growth compared to the subsector of agriculture in other Aceh provinces.While the most influential subsector is the forest subsector which is experiencing rapid growth in the Gayo Lues Regency. From the results of the study it was suggested that there should be attention by the local government and the need for better forest management in Gayo Lues District.Keywords : PDRB, Argiculture, Forestry, Fishery